Clinical and histological investigation ot' large hernial defects repaired with skin autograft in sheep: an experimental study - Fahrettin Alkan; Nuri Yavru; Cengiz Ceylan; İlhami Çelik; Murat Boydak; Yasemin Özkan (Eurasian Journal of Veterinary Sciences)
The aim of this experimental study was to evaluate the aplicability of autogenic skin graft in the treatment of large hernial defects in sheep. Total of 24 sheep used, were divided into 4 groups. Each groups had 6 sheep. Skin flaps, approximately 11 cm in diameter and 15 cm in length were removed over the umbilical area Consequently, hernial defect corresponding to the removed skin flap size, were created through the removal of abdominal musculuture and periton. Epidermal and dermal layers of skin flaps facing to the abdominal wall were placed in 3 sheep of each groups. Sheep were euthanized in 15, 30, 45 and 60 days, in groups 1. 2. 3 and 4, respectively. Following this, tissue samples were collected from different spots of autogen skin flaps and submitted for histologic evaluations. It was concluded thai skin autograft was superior to other hemioplasty materials because of the elasticity, easy applicability and inexpensiveness.